2011
DOI: 10.1002/ccd.23353
|View full text |Cite
|
Sign up to set email alerts
|

Staging of multivessel percutaneous coronary interventions: An expert consensus statement from the Society for Cardiovascular Angiography and Interventions

Abstract: Percutaneous coronary interventions (PCIs) to treat multivessel coronary artery disease (MVCAD) may involve single-vessel or multivessel interventions, performed in one or more stages. This consensus statement reviews factors that may influence choice of strategy and includes six recommendations to guide decisions regarding staging of PCI [1]. Every patient who undergoes PCI should receive optimal therapy for coronary disease, ideally before starting the procedure [2]. Multivessel PCI at the time of diagnostic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 124 publications
0
12
0
Order By: Relevance
“…This is the motivation for the aforementioned bundling experiments of Centers for Medicare and Medicaid Services. 6 According to Blankenship et al, 16 the Medicare physician and hospital payments for single-stage multivessel PCI are $1276 and $15 573, respectively, for in-patient procedures and for staged procedures the respective payments are $1906 and $31 146. Thus, the respective physician and hospital payments are 49% and 100% higher for staged procedures than for single-stage procedures.…”
Section: Discussionmentioning
confidence: 99%
“…This is the motivation for the aforementioned bundling experiments of Centers for Medicare and Medicaid Services. 6 According to Blankenship et al, 16 the Medicare physician and hospital payments for single-stage multivessel PCI are $1276 and $15 573, respectively, for in-patient procedures and for staged procedures the respective payments are $1906 and $31 146. Thus, the respective physician and hospital payments are 49% and 100% higher for staged procedures than for single-stage procedures.…”
Section: Discussionmentioning
confidence: 99%
“…The last decade has witnessed dramatic changes in how PCI is used in clinical practice [38-41], which is reflected in evolving guidelines [42]. The increasing use of drug-eluting stents as well as refinement in the optimal use of antiplatelet therapy [38-40, 42] mean that the long-term outcomes we report might differ were our study to be conducted today. Indeed, even the selection of appropriate PCI candidates may be changing, with an emerging belief that individuals with single vessel disease outside of the left anterior descending artery may not warrant PCI or even diagnostic catheterization [41].…”
Section: Discussionmentioning
confidence: 99%
“…National or private insurance committees in various countries tend to discourage staged procedures, especially if it is associated with readmission and, in real world clinical practice, numerous cardiologists have experienced rejection of reimbursements for the staged procedures in intermediate to very high risk patients with NSTE-ACS. It is obvious that staged procedures are associated with increased medical costs and previous studies reported that the medical cost of staged PCI is twice as expensive as that of onetime PCI 9)10). Therefore, in order to justify the extra medical cost of staged PCI for NSTE-ACS patients with multivessel disease, we need clear and robust evidences that staged PCI is better than one-time PCI in terms of clinical outcomes.…”
Section: Clinical Impact Of the Studymentioning
confidence: 99%